Seismic-Energy Combined Retrofit Systems of Historical Buildings: The Use of Light Metal Exoskeletons - Saracco, Ubaldo; Meglio, Emilia; Formisano, Antonio (Technical Annals, 2023)
The current trend in retrofitting existing buildings is mainly seen under the environmental aspect, giving little attention to seismic issues. Contrary, recent European Union’s policies in this field are based on integrated approaches aimed at improving both energy and earthquake performances. Therefore, the so-called seismic coats have been launched on the building market. In this framework, the design of a new system for seismic-environmental requalification of existing constructions made of masonry or reinforced concrete is presented and illustrated in the present paper through the application of a cold-formed steel framed structure. This system is provided with both insulation panels, used to provide energy benefits, and a X-bracing system, employed to absorb part of the seismic forces to preserve the existing structure from damage. In the current research work, firstly, a description of the coat’s components is presented. Secondly, the anti-seismic solution has been used to reinforce RC frames and its effectiveness has been proved by refined mechanical analyses in the non-linear field. Finally, the comparison of performances of examined structural system before and after the intervention has been made to evaluate the benefits provided by the proposed coating system under a seismic viewpoint.